Matrix Hard - The Impact of Technological, Economic and Social Indicators on Productivity and Competitiveness - Popa, Marina; Pisaniuc, Maia (International Journal of Applied Research in Management and Economics, 2020)
The objective of this research is to demonstrate the impact of technological, economic and social indicators on productivity and competitiveness through the HARD Matrix method, proposed by the European Commission. The level of economic development of different countries, as well as the degree of diversification and specialization of their world production, determines the degree of integration of national economies in the world economy that differs considerably by country and group of countries. The expansion and amplification of the internationalization process have substantially changed the place and role of each state in the world economy. Due to this process, today's world economy is no longer a simple sum of economies put in contact, but a global-universal system, unitary through the interrelationships between the component subsystems and its extremely heterogeneous structure. In the twenty first-century, the process of amplifying innovation, the net economy, and the Covid 19 pandemic have shaped new trends in the world countries and determined the balance of power between the three great empires of the world – the United States, the European Union, and China. At the same time, there are no similar links between the United States, the European Union and China, they do not share the same culture, do not share the same geographic space, and do not use the same models of economic development, but all of them consider innovation, sophisticated business, technology, safe tools in promoting economic growth and competitiveness.